PDF Hubungan Pengetahuan Dan Kecemasan Pandemi Covid-19 Terhadap Pengeluaran ASI Ibu Post Partum Di Wilayah Kerja Puskesmas Silih Naras Kabupaten Aceh Tengah Tahun 2021 - Ara, Ayu; Sari, Febriana; Mutiara, Juleha; Romaito Harahap, Ngarap Muliana; Suhaila, Datin (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
A study reported that depressive and anxiety symptoms in pregnant women after the declaration of the COVID-19 pandemic were higher than before the declaration of COVID-19. The purpose of this study was to see the relationship between knowledge and anxiety of the Covid-19 pandemic on postpartum mother’s milk production. This research is an analytical survey method, using a cross sectional design. Collecting data on the measurement of the mother’s level of anxiety through interviews. Statistical test using the chi square test, the degree of significance of p. values 0.05. The results of the study showed that there was a relationship between mother’s knowledge about Covid -19 with breast milk production, p value of 0.00. There is a significant relationship between maternal anxiety and breastfeeding with a p value of 0.04. Mother’s knowledge and anxiety about covid -19 is related to the expenditure of postpartum mother’s milk at the Silih Nara Health Center in 2021. It is recommended to post partum mothers to be more active in finding the right source related to covid-19.